PENGARUH PENGGUNAAN ELASTIC LUMBAL CORSET TERHADAP NYERI PUNGGUNG BAWAH PADA PEGAWAI ANGKAT-ANGKUT - Anggriani, Atika Febri; Septiani, Anissa Eka; Meidiani, Hersya (Tahta Media Group, 2025)
Background: Repetitive physical activity and non-ergonomic work postures in building store employees increase the risk of lower back pain. Elastic lumbar corsets are used as a method to reduce these complaints by providing stability to the lumbar area. Purpose: this study aims to determine the effect of using elastic lumbar corsets on lower back pain. Research methodology: quantitative research using a pre-experimental research type with a one-group pretest-posttest design method with a sample size of 18 selected using inclusion and exclusion criteria. Analysis of this research data using the Wilcoxon test. Result: the results of the hypothesis test showed a p value of 0.001 and the value <0.05, which means there is an effect of using elastic lumbar corsets on reducing the degree of lower back pain in lifting and transporting employees. Discussion: There is a limitation of back mobility, especially in lumbar flexion movements that are often performed in daily activities, and it is known to contribute to increased pain and the presence of abdominal pressure that helps reduce pain. Conclusion: elastic lumbar corsets are able to reduce the degree of lower back pain in lifting and transporting.